2020
DOI: 10.1038/s41586-020-2446-y
|View full text |Cite
|
Sign up to set email alerts
|

Systematic quantitative analysis of ribosome inventory during nutrient stress

Abstract: SUMMARY Mammalian cells reorganize their proteomes in response to nutrient stress via translational suppression and degradative mechanisms using the proteasome and autophagy systems 1 , 2 . Ribosomes are central targets of this response, as they are responsible for translation and subject to lysosomal turnover upon nutrient stress 3 – 5 . Ribosomal (r)-protein abundance (~6% of the proteome, ~… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 45 publications
7
90
0
Order By: Relevance
“…Levels of protein synthesis were measured by HPG incorporation ( Sherratt et al, 2017 ; An et al, 2020 ). Cultures were grown at 37°C in M9 media containing 1x M9 salt (49 mM Na 2 HPO 4, 22 mM KH 2 PO 4, 8.6 mM NaCl, 18.7 mM NH 4 Cl), 100 μM CaCl 2 , 1 mM MgSO 4 , 1x minimal essential medium (MEM) vitamin solution, 1x methionine biosynthesis inhibition amino acids (L-lysine (100 μg/ml), L-threonine (100 μg/ml), L-phenylalanine (100 μg/ml), L-isoleucine (50 μg/ml), L-leucine (50 μg/ml), and L-valine (50 μg/ml)), and 0.2% carbon source.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Levels of protein synthesis were measured by HPG incorporation ( Sherratt et al, 2017 ; An et al, 2020 ). Cultures were grown at 37°C in M9 media containing 1x M9 salt (49 mM Na 2 HPO 4, 22 mM KH 2 PO 4, 8.6 mM NaCl, 18.7 mM NH 4 Cl), 100 μM CaCl 2 , 1 mM MgSO 4 , 1x minimal essential medium (MEM) vitamin solution, 1x methionine biosynthesis inhibition amino acids (L-lysine (100 μg/ml), L-threonine (100 μg/ml), L-phenylalanine (100 μg/ml), L-isoleucine (50 μg/ml), L-leucine (50 μg/ml), and L-valine (50 μg/ml)), and 0.2% carbon source.…”
Section: Methodsmentioning
confidence: 99%
“…Levels of protein synthesis were measured by HPG incorporation (Sherratt et al, 2017;An et al, 2020).…”
Section: Measurement Of Bulk Translation Levelsmentioning
confidence: 99%
“…An autophagic mechanism seemed most plausible given that previous studies in S. cerevisiae have demonstrated that starvation conditions that inhibit mTOR signaling and stimulate autophagic flux result in enhanced ribosomal turnover by the autophagy pathway (Kraft et al, 2008). While mTOR-dependent degradation of ribosomes via autophagy does not appear to play a large role in regulating ribosomal abundance in mammalian cells (An and Harper, 2018;An et al, 2020), we directly evaluated if uS3 or uS5 ubiquitylation resulted in autophagy-dependent degradation of 40S ribosomal subunits. We first examined uS3 and uS5 protein levels upon RNF10 overexpression in parental or autophagy-deficient cells that are devoid of the critical ULK1 complex member, RB1CC1 (FIP200) (An et al, 2019).…”
Section: S Protein Degradation Is Autophagy Independentmentioning
confidence: 99%
“…While the clear sequestration of ribosomes within vacuoles has been reported 26 , whether mammalian ribophagy occurs is currently a point of contention. While one study reported containing ribosomes within autophagosomes and attributed their sequestration into autophagosomes to the receptor protein NUFIP1 39 , another showed only limited degradation of ribosomes by autophagy during nutrient stress 40 . Meanwhile, the proportion of ribosomal protein in yeast is an order of magnitude higher than that of mammalian cells 41 .…”
Section: Discussionmentioning
confidence: 99%